A Late Antique Ceramic Assemblage at Burgaz, Datça Peninsula, South‐west Turkey, and the 'Normality of the Mixed Cargo' in the Ancient Mediterranean. (29th April 2015) - Leidwanger, Justin; Greene, Elizabeth S.; Tuna, Numan
<x xml:space="preserve">Abstract</x> By combining underwater survey with formal and compositional study of ceramics, recent work at Burgaz (south‐west Turkey) reveals a late 6th‐ or 7th‐century assemblage of wine and perhaps other agricultural products carried in LR1 and LR2‐related amphoras. Representing various south‐east Aegean and likely Cilician producers, the mixed cargo aboard this probable shipwreck offers insights into the complex dynamics of seaborne distribution at the end of Antiquity. This brief study also underscores the need for documentation in underwater survey of amphora forms and fabrics, particularly those from a period characterized by intensified and diversified production of supra‐regional ceramic types.